UTILIZATION OF SWINE DEEP BEDDING ASHES AND RICE HUSK IN CEMENTITIOUS COMPOSITES - OLIVEIRA, D. C. G.; SAVASTANO JUNIOR, H. (Revista Brasileira de Engenharia de Biossistemas, 2013)
The swine deep bedding is an alternative pig production, especially during the growing and finishing pig, whose product can be recycled, with reduced environmental impact. Usually the waste being used as fertilizer for crops, can alternatively be combusted and its ashes can be applied to materials based on cement. Therefore, the objective of this study was to evaluate the use of swine deep bedding ashes for replacement partial of Portland cement and rice husk its interaction through physical and mechanical characterization. Were prepared four sets of specimen: C1 - control (Portland cement and sand), C2 - control with 30% of SDBA, C3 - control with HR, C4 - control with 30% SDBA and RH; the ashes replaced the Portland cement and rice husk the sand. According to the results of characterization, the composite with the addition of swine deep bedding ashes and rice husk can be used in rural constructions.